Conceptual Metaphor of Different Conventionality Levels from the Perspectives of Translatability Assessment and Translation Strategies - Thong Vi Nguyen; Nguyen Thi Thao Hien (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2022)
This study examines the Conceptual Metaphor Theory from an innovative perspective: translatability and translation strategy. The experiment recruited 239 undergraduate students of different translation training to evaluate the translatability of twelve sentences of different metaphor types before translating them into Vietnamese. Additionally, this study examines how students deal with metaphorical mapping images as well as grammatical and lexical refining attempts. The factorial ANOVA results (p=.02) indicate that the effect of metaphor types on translatability levels is conditional on translation training levels, despite the fact that the main effect is on metaphor types, not translation skill. Besides, twelve in-depth strategies to deal with the source sentences are identified, establishing a new model for metaphorical translation strategy. Chi-square analysis reveals associations between translation training levels and strategies (p<.01); and between metaphor types and strategies (p<.01). This study argues for the possibility that translation could be considered among conceptual metaphor's cognitive mechanisms.